Digital Transformation in Public Administration: Challenges and Opportunities in Indonesian Government Agencies - Syafaruddin Syafaruddin; Andi Riska Andreani Syafaruddin; Nurasia Natsir (Harmony Management: International Journal of Management Science and Business, 2026)
The digital transformation of public administration represents a critical pathway toward modernizing governance, enhancing service delivery, and improving transparency in Indonesian government agencies. This study examines the current state of digital transformation initiatives across various levels of government in Indonesia, identifying key challenges and opportunities in implementing digital technologies within bureaucratic structures. Through a convergent parallel mixed-methods design combining surveys of 245 government officials from 32 agencies and in-depth interviews with 28 digital transformation leaders, this research reveals that while Indonesian government agencies have made significant progress, substantial barriers remain including limited digital infrastructure in remote regions, resistance to organizational change, insufficient digital literacy among civil servants, and inadequate legal frameworks. The overall mean maturity score was 2.87 (SD = 0.74), placing the average agency in the 'developing' category, with only 6% reaching the 'optimizing' level. The study identifies critical success factors: strong leadership commitment (β = 0.38, p < 0.001), citizen-centric design, comprehensive change management, and effective public-private partnerships. Findings indicate that successful digital transformation requires not merely technological adoption but fundamental organizational restructuring and cultural shifts toward data-driven decision-making and collaborative governance. Policy recommendations address digital infrastructure investment, human capital development, governance reform, and shared platform utilization. This research contributes to theoretical understanding of digital government in developing nations and provides practical guidance for policymakers navigating the complexities of public sector digitalization.